The Art of Antithesis in Surah Al-Layl: A Descriptive Rhetorical Analysis - Wahyudi, Muhammad; Hasanah, Cindy Aulia; Khairunnisa, Nazua; Alvisan, Diva Alyasmin Qolbi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study analyzes the use of ṭibāq (semantic opposition) in Surah Al-Lail from the perspective of balāghah (Arabic rhetoric). Previous studies on ṭibāq in the Qur’an generally focus on long chapters; therefore, this research is significant for highlighting rhetorical beauty in a short surah rich in meaning, an aspect that has received little scholarly attention. The purpose of this study is to explain the forms of ṭibāq found in Surah Al-Lail and to understand their aesthetic and rhetorical functions in reinforcing the moral messages of its verses. The research employs a qualitative approach with a library research method, utilizing primary sources such as the Qur’an, Jāmiʿ al-Bayān by al-Ṭabarī, al-Kashshāf by al-Zamakhsharī, and academic literature on Qur’anic stylistics. Content analysis was conducted to identify, classify, and interpret the forms of ṭibāq appearing in the surah. The findings reveal the presence of both positive and negative ṭibāq, such as contrasts between “night” and “day,” “giving” and “withholding,” as well as “the easy path” and “the difficult path.” The use of ṭibāq clarifies semantic contrasts, strengthens moral messages, and enhances rhetorical impact. Thus, this study contributes to a deeper understanding of the stylistic function of ṭibāq in short surahs and reaffirms the relevance of balāghah.